2019
DOI: 10.1186/s12889-019-7895-6
|View full text |Cite|
|
Sign up to set email alerts
|

Going upstream – an umbrella review of the macroeconomic determinants of health and health inequalities

Abstract: BackgroundThe social determinants of health have been widely recognised yet there remains a lack of clarity regarding what constitute the macro-economic determinants of health and what can be done to address them. An umbrella review of systematic reviews was conducted to identify the evidence for the health and health inequalities impact of population level macroeconomic factors, strategies, policies and interventions.MethodsNine databases were searched for systematic reviews meeting the Database of Abstracts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 85 publications
(95 reference statements)
2
65
0
3
Order By: Relevance
“…Specifically, the business practices of corporations include, amongst other things, the control of the supply chain and market concentration (through mergers and acquisitions for example); labour practices; taxation payments and profits shifting; and the privatisation of utilities [1,13,15,41]. In 2018, Wiist explained that corporate tax avoidance, for example, leads to a shortage of public tax revenue that could be directed to public health purposes and other needs, such as education and housing [42].…”
Section: Corporations and Practices Harmful To Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the business practices of corporations include, amongst other things, the control of the supply chain and market concentration (through mergers and acquisitions for example); labour practices; taxation payments and profits shifting; and the privatisation of utilities [1,13,15,41]. In 2018, Wiist explained that corporate tax avoidance, for example, leads to a shortage of public tax revenue that could be directed to public health purposes and other needs, such as education and housing [42].…”
Section: Corporations and Practices Harmful To Healthmentioning
confidence: 99%
“…These global drivers indeed influence the business, market, and political practices of corporations, therefore facilitating the manufacture, sale and marketing of unhealthy commodities [ 1 ]. Market-driven and neoliberal economies, globalisation, and the development of trade and investment agreements, amongst other factors, have for example contributed to the growing power of corporations in recent decades, but also to the ill-health for the population and planet [ 22 , 41 , 72 – 76 ]. Transnationals, in particular, control their markets in many countries, some markets being saturated, and others, in low- and middle-income countries, emerging [ 22 , 34 , 77 80 ].…”
Section: The Commercial Determinants Of Healthmentioning
confidence: 99%
“…Research suggests that public social spending ( Hillier-Brown et al, 2019 ) and income inequality ( Naik et al, 2019 ) are social determinants of population health. These macro determinants vary by welfare states and are included to complement our regime approach ( Bergqvist, Yngwe, & Lundberg, 2013 ).…”
Section: Methodsmentioning
confidence: 99%
“…39 Naik et al, 2019, reviewed the evidence on the influence of high-level economic factors such as markets, finance, the provision of welfare, labour markets and economic inequalities on people's health and health inequalities. 38 The authors found evidence that the risk of dying from any cause is significantly higher for people living in socioeconomically deprived areas than for those living in areas with high socioeconomic status. They also found good evidence that wide income inequality is associated with poor health outcomes.…”
Section: The Current Evidence Basementioning
confidence: 99%